Training on the Design of Educational Animated Media as an Effort to Improve Teacher Quality at Tadika Al-Fikh Orchard, Malaysia - Setiawan, Hasrian Rudi; Hasan, Ibrahim; Maysarah, Maysarah (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (PKM) aims to improve the quality and competence of teachers at Tadika Al-Fikh Orchard, Malaysia through training on the design of educational animated media. The rapid development of digital technology requires early childhood education teachers to deliver learning experiences that are creative, interactive, and aligned with students’ characteristics. However, many teachers still face limitations in designing and utilizing animation-based learning media effectively. The implementation methods of this program include training sessions, mentoring, and hands-on practice in developing educational animated media using accessible digital design applications. The results indicate an improvement in teachers’ understanding and skills in designing animated learning media, as well as increased creativity in delivering engaging and innovative learning materials. This training is expected to contribute to enhancing the quality of learning and teacher professionalism at Tadika Al-Fikh Orchard.